Mitochondrial DNA damage induced autophagy, cell death, and disease - Van Houten, Bennett (Front Biosci (Landmark Ed), 2016)
Mammalian mitochondria contain multiple small genomes. While these organelles have efficient base excision removal of oxidative DNA lesions and alkylation damage, many DNA repair systems that work on nuclear DNA damage are not active in mitochondria. What is the fate of DNA damage in the mitochondria that cannot be repaired or that overwhelms the repair system? Some forms of mitochondrial DNA damage can apparently trigger mitochondrial DNA destruction, either via direct degradation or through specific forms of autophagy, such as mitophagy. However, accumulation of certain types of mitochondrial damage, in the absence of DNA ligase III (Lig3) or exonuclease G (EXOG), enzymes required for repair, can directly trigger cell death. This review examines the cellular effects of persistent damage to mitochondrial genomes and discusses the very different cell fates that occur in response to different kinds of damage.